EFFECT OF SONIC BOOMS OF VARYING OVERPRESSURES ON SNOW AVALANCHES - FEDERAL AVIATION AGENCY WASHINGTON DC (1965)
On 18 - 20 March 1965, a sonic boom program was conducted in the Star Mountain area near Leadville, Colorado, in the San Isabel National Forest. Objective was to determine the effects of sonic boom overpressures on snow avalanches. A total of 18 combined F-104 and F-100 runs were made with overpressures ranging from 1.5 to 5.2 measured. No avalanche was observed as a direct result of the sonic booms. Forest Service personnel rated the avalanche hazard as "low" during the test period, resulting in the recommendation for further tests during periods of "high" avalanche hazard. Prepared in cooperation with Forest Service, Washington, DC., Department of the Air Force, Washington, DC. and National Aeronautics and Space Administration, Washington, DC.